“Friends? or enemies? Deconstructing the enemy" - Zozaya-Montes, Maria (2018)
English: An analysis of a part of the Peninsular war that has been little studied, that of the Spanish prisoners in France, is here presented. Within the scope of a needed revision, how the image that some military engineers had of the French people (as friends) will be shown, which does not correspond to the official version (as enemies) normally accepted. Español: En la guerra de la Independencia y a raíz del caso de los prisioneiros de Guerra españoles por los ejércitos de Napoleón se analiza el paso del concepto de enemigo al de amigo, una visión que normalmente há sido borrada de la memoria colectiva de la Guerra.